2015
DOI: 10.5152/turkpediatriars.2015.2795
|View full text |Cite
|
Sign up to set email alerts
|

Desire to have other children in families with a chronically disabled child and its effect on the relationship of the parents

Abstract: Aim: The aim of this study was to examine the desire of the parents who had a chronically disabled child to have other children and to investigate the effect of having a disabled child on the relationship of the parents. Material and Methods:The families of 145 chronically disabled children were included in the study. After the sociodemographic information belonging to the child and family were obtained, the prepared questionnaire form was used to interrogate if the parents lived together, the number of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…According to a study conducted in Turkey, 66.20% of mothers of children with disabilities stated they did not want to have children again, while 33.80% stated that they wanted to have children again. 18 In our study, 79.30% of mothers whose first child had a disability wanted to have more children, while 74.60% of mothers whose last child had a disability did not want to have more children. When those with one child were excluded from the group of parents whose first child had a disability, the percentage of those not wanting to have more children rose to 86.70%.…”
Section: Discussionmentioning
confidence: 46%
“…According to a study conducted in Turkey, 66.20% of mothers of children with disabilities stated they did not want to have children again, while 33.80% stated that they wanted to have children again. 18 In our study, 79.30% of mothers whose first child had a disability wanted to have more children, while 74.60% of mothers whose last child had a disability did not want to have more children. When those with one child were excluded from the group of parents whose first child had a disability, the percentage of those not wanting to have more children rose to 86.70%.…”
Section: Discussionmentioning
confidence: 46%
“…Parents of children with trisomy 13 or 18 reported a divorce rate of only 3%, whereas 68% reported positive effects on their relationship [ 10 ]. In a Turkish study, the divorce rate of parents with a disabled child were low and most reported positive effects on their relationships [ 33 ]. Therefore, the available data do not support the idea that having a disabled child increases divorce rates.…”
Section: Framework For Counseling Of Parentsmentioning
confidence: 99%